PBL-Based Animation Video Media to Improve Elementary School Students' Problem-Solving Skills - Sholikhah; Joko Sulianto; Joko Siswanto (Jurnal Pendidikan dan Pengajaran, 2026)
Learning media is an important component for increasing the effectiveness of student-centered learning because it serves as a mediator between teachers and students in understanding learning materials. This study aims to analyze and test the effectiveness of animation video media based on Problem Based Learning (PBL) in improving students' problem-solving skills and cognitive learning outcomes. This research is a development study (Research and Development) using the ADDIE model, which includes the stages of Analyze, Design, Development, Implementation, and Evaluation. The research subjects consisted of elementary school students and teachers who were involved in the trial of learning media. Data were collected through validation sheets, response questionnaires, as well as pretest and posttest. Data analysis used N-Gain to determine the improvement in learning outcomes and t-test to examine the effectiveness of the media. The results of the study showed that the PBL-based animation video media developed received a very good category based on assessments from media experts and material experts. The implication of this research indicates that the use of PBL-based animation video media can be an innovative learning media alternative that helps teachers in improving problem-solving skills as well as students' cognitive learning outcomes.